24 Common and Rare Variation in the T Helper 2 Gene Pathway Predicts Allergic Asthma Phenotypes - Slager, Rebecca (World Allergy Organization Journal, 2012)
BACKGROUND: The T helper 2 (Th2) inflammatory pathway, including the Th2-activating cytokine interleukin 33 and its receptor interleukin 1 receptor-like 1 have been strongly implicated in asthma susceptibility (Moffatt MF, et al NEJM 2010). However, the role of Th2 pathway genetic variation in asthma progression and severity is not well understood. Our research group recently developed a clustering algorithm based on comprehensive phenotype information to assign subjects with asthma in the Severe Asthma Research Program (SARP) to 5 primary clusters; 3 of which represent increasing severe allergic asthma (Moore WC, et al AJRCCM, 2010). We hypothesized that common and potentially deleterious rare variation in this pathway would be associated with severe asthma based on SARP cluster designation. METHODS: To evaluate common variants (minor allele frequency or MAF >5%), 419 SARP non-Hispanic white participants with a cluster assignment were genotyped for 182 single nucleotide polymorphisms (SNPs) in Th2 pathway genes using whole-genome SNP data. Individual SNPs and a cumulative model of significant SNPs were evaluated using contingency tables with a chi-square test for trend and ordinal regression models adjusted for age, sex, and principal components. Rare (MAF <5%) amino acid changes and splice site alterations in this pathway were tested for association with asthma severity outcomes in 20 SARP subjects with whole exome sequence data. RESULTS: Individual Th2 pathway variants were associated with overall SARP cluster assignment, and allergic clusters of increasing severity (1, 2, and 4), including GATA3 polymorphism rs1244186 (P = 0.005). In an 18-SNP additive model, an increasing number of Th2 pathway risk genotypes were highly associated with severe allergic asthma (P = 3.9 × 10(−6)). For example, in cluster 4, the percentage of subjects with at least 9 risk genotypes was 83% compared to 35% in cluster 1. Additionally, there was evidence that subjects with rare variants in this pathway were more likely to report allergy symptoms (P = 0.006), especially in the fall (P = 0.003), compared to subjects with no rare variants. CONCLUSIONS: Common Th2 pathway variants predict an increased likelihood of severe allergic asthma and rare variants were associated with increased seasonal allergy symptoms.